Cadangan Remaja Perempuan Mengenai Persediaan Untuk Mengbadapi Haid - Ismail, Maznah (Penerbit Universiti Sains Malaysia, 1997)
One of the major events in the life of a girl is the onset of menstruation or menarche. This paper examines adolescent girls' recommendations with respect to preparation for menarche. The sample consisted of 152 secondary school girls. the majority of whom had been menstruating for about three years. They had to respond to an open-ended questionnaire which among other things. asked what kind of help should be given to a person going through the experience the first time.